Career Persistence Model for Female Engineers in the Indonesian Context - Dahlia, Lies (Universitas Prasetiya Mulya, 2017)
Extant studies about female engineers have suggested their career persistency in the engineering career is influenced by the workplace, which is characterized by male dominated culture making them feel marginalized. In Indonesia, similar studies for reference are limited. This paper is based on an exploratory quantitative study using a questionnaire developed based on the Career Persistence Model. This paper is based on an empirical exploratory quantitative study by adopting Buse’s et al. Career Persistence Model (2013). The intention is to contribute to the literature in the context of Indonesia. It explores the Indonesian cultural dimensions and investigates their relationship to the roles of women in family, society and the workplace, and how women manage to navigate barriers to avoid taking alternative career paths. Contrary to extant studies, findings show women feel equally treated to men in the workplace, however some work demands may hinder. The strong acknowledgement of one’s roles in this collective society outdoes the opinions that the Islamic jurisprudence (fiqh) has marginalized empowerment of women, resulting in gender-based injustices and discrimination. Future studies should look into social supports at the workplace in an attempt to retain and increase the share of women in the engineering career in Indonesia).